Improving Handover in GSM Network - Sharma, Giriraj; Bansal, Ashish Kumar; Jhalani, Ankur (International Journal of Emerging Trends in Science and Technology, 2014)
All GSM service provider uses KPI to monitor their QOS performance. Report generated from OMCR terminal & customer feedback are considered in further network improvement activity. Handover is very important QOS .In this paper some practical cases and solutions are adopted to improve theÂ Handover . Major Handover failure reason, call drop, easons and solutions are discussed. drive test tool Ascom TEMS 10.2.1 is used to perform drive test. if optimization done continuously it will attract more and more customers due to service satisfaction. Index term :- GSM,RF optimization ,drivetest, TEMS drive test tool, Handover etc.